2008
DOI: 10.4137/sart.s1044
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Suicidal Behavior and Substance Use: Developmental Mechanisms

Abstract: Adolescent suicidal behaviors and substance use are disturbingly common. Research suggests overlap of some of the etiological mechanisms for both adolescent suicidal behavior and substance use, yet clear understanding of the complex relations between these behaviors and their causal underpinnings is lacking. A growing body of evidence and a diathesis model (Mann et al. 1999;Mann, 2003) highlight the importance of impulse control as a proximal risk factor for adolescent suicidal and substance use behaviors. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 186 publications
(224 reference statements)
3
31
0
Order By: Relevance
“…Associations with lifetime suicide attempts may partly reflect other psychiatric morbidity, including anxiety disorders and depression. However, they also correspond to the notion that impulsive violence may be directed both outward and inward (24). The relationship between alcohol misuse and violence is highly complex (25).…”
Section: Discussionmentioning
confidence: 88%
“…Associations with lifetime suicide attempts may partly reflect other psychiatric morbidity, including anxiety disorders and depression. However, they also correspond to the notion that impulsive violence may be directed both outward and inward (24). The relationship between alcohol misuse and violence is highly complex (25).…”
Section: Discussionmentioning
confidence: 88%
“…Thus, it appears the more lethal the behavior among the Apaches, the greater the cooccurrence with alcohol and drug use. While explanations from the literature could attribute this fact to the loss of impulse control that comes with substance use (2,9), Apache collaborators seek more culturally relevant explanatory models that posit substance abuse as a co-occurring form of adolescent self-injury that amplifies results of intentional self-harm. This idea is in contrast to dominant Western models of suicide, such as Joiner's (10) and Mann et al's (11), that do not include binge substance use in the spectrum of self-injury.…”
Section: Discussionmentioning
confidence: 98%
“…A broad literature supports that suicide and substance use co-occur (1). However, the relationship and possible shared causes are unknown (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, suicidal ideation and substance use may affect each other (Dawes et al, 2008). Findings from three longitudinal studies found earlier substance use predicting later suicidal ideation, but did not support the reverse relations (van Ours et al, 2013; Pederson and von Soest, 2008; Bronisch et al, 2008).…”
Section: Introductionmentioning
confidence: 99%